KARAKTERISTIK ANTIBAKTERI MINYAK ESSENSIAL DAUN DRIMYS PIPERITA TERHADAP PERTUMBUHAN BAKTERI RESISTEN ANTIBIOTIK - Gino Nemesio Cepeda (AGROINTEK, 2021)
Akway (Drimys piperita Hook. f) is an aromatic plant that contains essential oils in leaves and stem barks parts. The objectives of the research were to evaluate charakteristic of essential oils obtained from akway leaves as natural antibacterial agent for inhibiting growth of pathogenic bacteria namely Escherichia  coli, Pseudomonas aeruginosa, Bacillus  cereus  and Staphylococcus aureus in some levels of concentrations, acidity (pH) and sodium chloride concentrations. The extraction process of essential oil leaves was done by using hydrodistillation method. Antibacterial assays were perfomed using agar well diffusion method. The results indicated that Essential oil of akway leaves can inhibited all bacteria tested. Antibacterial characteristic of akway leaves essential oil increased as the concentration increased. Variation of pH 4-8,5 and sodium chloride concentrations up to 5% did not affected antibacterial properties of akway leaves essential oil.